Synergistic role of anti-inflammatory diet and physical activity in modulating chronic pain syndromes – a narrative review - Pietrzyk, Małgorzata; Nawrocka, Natalia; Hojda, Alicja; Bednarek, Filip; Małajewicz, Izabela; Plinta, Olga; Stępień, Dawid; Rodak, Hanna; Oskroba, Karolina (Quality in Sport, 2026)
Background: Chronic pain affects ~20–30% of adults and is increasingly viewed as a disease entity (ICD-11). Low-grade systemic inflammation and central sensitization are key mechanisms; therefore, lifestyle measures such as an anti-inflammatory dietary pattern and regular physical activity may modulate pain-related pathways. Aim: To summarize evidence on anti-inflammatory diet and physical activity in chronic pain, focusing on clinical trials and systematic reviews. Methods: Narrative review of PubMed, Web of Science and Google Scholar (to November 2025) using terms related to chronic pain, anti-inflammatory/Mediterranean diet, Dietary Inflammatory Index (DII), fibromyalgia, low back pain, osteoarthritis, and exercise therapy. Priority was given to randomized trials, cohort studies, systematic reviews and meta-analyses in adults. Results: Higher-quality anti-inflammatory diets rich in vegetables, fruit, whole grains, plant proteins and omega-3 fatty acids are associated with lower inflammatory burden and modest improvements in pain and quality of life in non-cancer chronic pain (e.g., rheumatic pain, osteoarthritis, low back pain). Pro-inflammatory DII scores correlate with greater systemic inflammation and poorer health status. Meta-analyses also support benefits of aerobic and resistance training, motor-control exercise, walking and aquatic exercise for reducing pain and improving function and quality of life, particularly in chronic low back pain and fibromyalgia. Combined programs integrating diet, exercise and education appear especially promising. Conclusions: Anti-inflammatory diet and regular physical activity are complementary, important components of non-pharmacological chronic pain management, but more high-quality randomized trials are needed to test integrated, phenotype-informed lifestyle interventions and account for psychosocial factors.